The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0100-69912006000500003
|View full text |Cite
|
Sign up to set email alerts
|

O sistema Apache II e o prognóstico de pacientes submetidos às operações de grande e pequeno porte

Abstract: RESUMO: Objetivo: Geral: avaliar o desempenho do sistema APACHE II no pré-operatório de operações de grande e pequeno porte como indicador prognóstico. Os objetivos secundários são: (a) avaliar o sistema no pré-operatório para predizer morbidade; (b) comparar resultados entre os dois grupos e; (c) comparar a mortalidade observada com a esperada, calculada pela Equação de Knaus. Método: Estudo de coorte prospectivo, por 30 meses. No Grupo 1, correspondente à operação de pequeno porte, incluídos 30 pacientes sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The association between these data influenced the overall mortality. Castro Júnior et al concluded that patients with an APACHE II score greater than eight and subjected to large operations may present a high rate of morbidity and mortality 12 , resembling these data.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The association between these data influenced the overall mortality. Castro Júnior et al concluded that patients with an APACHE II score greater than eight and subjected to large operations may present a high rate of morbidity and mortality 12 , resembling these data.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 70%
“…There may be significant variability in assessing perioperative ASA, collaborating in patient management. In the ICU, the APACHE II (Acute Physiology and Chronic Health Evaluation) is widely used, collaborating with the planning of the patient care [11][12][13] . The initial diagnosis is essential for risk adjustment.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
See 1 more Smart Citation